The rules and controls for accepting good deeds in a changing world - Alfailakawi, Yaqoub Yousef (Journal of Islamic Sciences, 2021)
In this research, I aimed to present the most important endeavours of a Muslim slave in his life. the collection of good deeds and care to accept good work; According to the Holy Koran and the right prophetic year; This can only be done in the words and good deeds to which the Muslim good luck in this life. Without ignorance or negligence in the light of the terms and conditions of this, Knowledge of God's greatness avoids a Muslim to fall into such oblivion. Happiness and satisfaction can only be achieved through devotion to the laws of Islam. It also outlined the variables of the times and their impact on the acceptance of good work, To that end, I have followed the descriptive extrapolation approach in my research, and I have divided it into three Reports.
Keywords: Controls; Good deed; good work; A Changing World